ANALISIS KARAKTERISTIK SISTEM AGROFORESTRI LAHAN GAMBUT DI KELURANGAN KALAMPANGAN - Nurlyanti, Arief; Arifin, Yudi Firmanul; Kissinger, Kissinger (Lambung Mangkurat University-Indonesia, 2024)
Destruction of forests and peat swamp lands in Indonesia is currently continuing, while restoration efforts have not yet produced real and satisfactory results. The rate of recovery of the peat ecosystem has still not been able to catch up with the rate of damage, which is increasingly worrying, especially due to fires that occur almost every dry season. This condition also occurs in Central Kalimantan Province, where peat ecosystem degradation has reached more than 35%. This research was conducted in Kalampangan Village, Sabangau District, Palangkaraya City, Central Kalimantan Province which is included in the Kahayan-Sebangau Peat Hydrological Unity (KHG) area. The methods used in this research were field observations, sampling in the field, making measuring plots (PU), interviews, key informants, research reports, journals, maps from the Central Kalimantan Provincial Forestry Service, data from the Central Statistics Agency. The results of the research are that the agroforestry system developed by farmers in Kalampangan Subdistrict can be classified into 6 (six) categories, namely: (1) agrisilviculture, with 4 (four) planting patterns; (2) agrosilvofishery, with 3 (three) planting patterns; (3) silvopasteur, with 3 (three) planting patterns; (4) agrofishery, with 1 (one) cultivation pattern; (5) apiculture, with 2 (two) cultivation patterns; and (6) Agropasturasilvofishery. One of the important components of the agroforestry system that has been developed by farmers in all peatland physiographies is fruit plants. The types of fruit plants that farmers have cultivated in each peatland physiography can be combined with experiences from other peat areas.